Praktik Jurnalisme Robot Sebagai Akhir Profesi Jurnalis - Utoyo, Arsa Widitiarsa; Putranto, Algooth (Jurnal Mahardika Adiwidia, 2022)
Major media corporations in the West have begun to use AI (Artificial Intelligence) to write news. In Indonesia, news site Beritagar.id is the first to use AI to write news. Is "artificial intelligence" technological development the final sign of human role as news reporters? For science fiction genre film fans, Skynet artificial intelligence or AI system is familiar in the Terminator trilogy. Determinism of technology can be interpreted as due to the influence of technological developments. Moreover, it can not be denied that the presence of cyber media and citizen journalism movement directly or indirectly impacts the media that has been considered the ruler of information production and distribution. This condition occurs because the internet provides easy access to citizens by accessing information, producing information, and even producing news produced, causing the pattern of social democracy to change.Â